Foresight Scanning: Future Directions of Clinical and Pharmaceutical Research - Brian C. Foster (Journal of Pharmacy & Pharmaceutical Sciences, 2009)
Foresight Scanning: Future Directions of Clinical and Pharmaceutical Research.